Public Discipline and Security System in The "Old City" of Tashkent (Late 19th – Early 20th Century) - Tangirov Obid Eshmaxmatovich (Pubmedia Social Sciences and Humanities, 2025)
During the late 19th and early 20th centuries, the responsibility for maintaining peace and security in the “Old City” of Tashkent rested with the district oqsoqol, who carried out these duties by relying on mirshabs and yigits. The appointment of yigits was made by the city chief based on the recommendations of the oqsoqol. This study examines the evolution of public discipline and security systems in the "Old City" of Tashkent during the late 19th and early 20th centuries under Russian colonial rule. It analyzes the imposition of new administrative and legal frameworks, the transformation of traditional forms of social control, and the impact of these changes on the daily lives of the local population. Key aspects explored include the establishment of police forces, the implementation of regulations concerning public order, and the responses of the local community to these measures. The research draws on archival documents, contemporary accounts, and scholarly literature to provide a comprehensive overview of the dynamics of power and social control in this critical period of Tashkent’s history